Performance and tibia characteristics of chickens fed cassava chips supplemented with Dl-methionine (2016)
This study was carried out to investigate the effect of cassava chips and DL-methionine supplementation on performance and tibia bone characteristics of broiler chickens. Broiler chickens were randomly assigned to 20 treatments in a 4x5 factorial arrangement with 5 dietary levels of cassava chips (0, 25, 50, 75 and 100 corn replacement) and 4 dietary levels of DL-methionine supplementation (0, 0.05, 0.1 and 0.2% i.e. 0, ½ NRC, NRC and double NRC 1994 recommended levels). Data obtained were subjected to analysis of variance. At starter phase, birds on cassava chips-based diets had significantly (P<0.05) higher body weight gain (BWG) than the control. Those on 25% cassava chip-based diet compared well with the control. Methionine supplement improved BWG at both starter and finisher phases; Cassava chips supplemented with DL-methionine can replace corn 100.00% in broiler chickens diet.